Educação de Surdos no âmbito da Superintendência Regional de Educação de Nova Venécia/ES : a formação de professores em foco - Lacerda, Lara Regina Cassani (2019)
The research aims to critically understand the challenges and possibilities that permeated the schooling of deaf people in schools under the Regional Superintendence of education of Nova Venécia/ES and, through the contributions of professionals who work in these schools, to find essential grounds to the continuing formation of these subjects. As it is a professional master's degree study, it assumes, as a final product, the systematization of a continuing education proposal in context, which promotes interactions between the educational legislation (national and local), the experience in schools and the educational literature. The study has the theoretical contributions of Boaventura de Sousa Santos (2006, 2007, 2010), Philippe Meirieu 2002, 2005) and authors who directly discuss special education and deafness, such as Skliar (1999, 2016), Quadros (1997, 2004, 2006, 2009) and Lacerda (1998, 2006, 2009). The theoretical-methodological reference involves a qualitative approach, through a case study. For data collection, it uses documentary analysis, the composition of moments of continuing formation and the realization of focal groups and interviews. The subjects involved in the research process in formative moments were a pedagogical technicians and a school supervisors of the Regional Superintendence of Education, pedagogues, coordinators and specialized educational service teams working in schools linked to the superintendence of Nova Venécia. Once, interviews were conducted with a school supervisor and a pedagogical technique of this regional institution. The data collection period was effective between July and December 2018. As results, in the narratives collected in the focal group and in the interviews, we searched for cross-linked data with the guiding documents of the inclusion of deaf, emerging a course of continuing formation, composed based on the reports of the professionals who were heard in the focal group, based on their experiences and formative needs within the challenges and possibilities experienced in the everyday school in which they are involved. Thus, it is evident the need for continuing formation in context, highlighting, based on the narratives collected in the field, that the themes arising from the dialogues with the subjects surveyed could compose four modules of the training proposal, presented as the real needs of the group: 1) Right to education and schooling: dialogues with current legislation and the diffusion of Libras in schools; 2) Literacy of deaf people in common school and the approach of Libras and Portuguese language in the schooling of deaf people; 3) Support networks: articulation of specialized educational service with the classroom, attributions and contributions in the schooling of the deaf; 4) Curriculum, pedagogical practices and evaluation: challenges and tensions in the schooling of deaf people. In the composition of the modules of the formative proposal, the challenges and possibilities that cross the schooling of the deaf in the researched region are evident. Thus, the study achieves its objective and proposes an intervention that can contribute to the transformation of this reality.